2013
DOI: 10.4236/ce.2013.410090
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Students’ Learning Styles to Their Academic Success

Abstract: This study was aimed to evaluate the learning styles of education faculty students and to determine the effect of their success and relationship between their learning styles and academic success. The population of this study is comprised of the students of Education Faculty in 19 May University and the sample includes 140: 68 art, 72 preschool teacher department students. Depending on the results obtained from pre-test, it was aimed to improve students' knowledge and skills in studying. There was a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 21 publications
1
38
0
6
Order By: Relevance
“…Bazı çalışmalarda akademik başarı ve öğrenme stilleri arasında ilişki bulunmasına karşın (Atkinson, 1998;Avsec ve Szewczyk-Zakrzewska, 2017;Freiberg-Hoffmann, Stover ve Donis, 2017;Hernández-Torrano, Ali ve Chan, 2017;Ross, Drysdale ve Schulz, 2001;Sapancı, 2014;Yılmazel, Büyükkayacı Duman ve Başçı, 2015), bu çalışmada akademik başarının incelenmesinin amacı hangi öğrenme stilinin ya da bilişsel stilin daha işe yarar olduğunu ortaya koymak değil, daha çok öğreten ve öğrenen arasındaki ilişki ile ilgili öngörüde bulunmaktır. Literatürde öğrenme stilleri dikkate alınarak hazırlanan programlarda (Birrell vd., 1985;Burns vd., 1998;Fan vd., 2015;Gökalp, 2013;Hein ve Budny, 2000;Horton ve Oakland, 1997;Komarraju vd., 2011;Özgen ve Alkan, 2014;Reynolds ve Gerstein, 1992;Uzuntiryaki, 2007;Yazıcılar ve Güven, 2009), daha yüksek akademik başarın elde edildiği belirtilmektedir. Bu çalışmada ayrıştırma öğrenme stiline sahip öğrencilerin genel akademik başarı puan ortalamaları diğer öğrenme stillerine sahip öğrencilerin genel akademik başarı puan ortalamalarından yüksektir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bazı çalışmalarda akademik başarı ve öğrenme stilleri arasında ilişki bulunmasına karşın (Atkinson, 1998;Avsec ve Szewczyk-Zakrzewska, 2017;Freiberg-Hoffmann, Stover ve Donis, 2017;Hernández-Torrano, Ali ve Chan, 2017;Ross, Drysdale ve Schulz, 2001;Sapancı, 2014;Yılmazel, Büyükkayacı Duman ve Başçı, 2015), bu çalışmada akademik başarının incelenmesinin amacı hangi öğrenme stilinin ya da bilişsel stilin daha işe yarar olduğunu ortaya koymak değil, daha çok öğreten ve öğrenen arasındaki ilişki ile ilgili öngörüde bulunmaktır. Literatürde öğrenme stilleri dikkate alınarak hazırlanan programlarda (Birrell vd., 1985;Burns vd., 1998;Fan vd., 2015;Gökalp, 2013;Hein ve Budny, 2000;Horton ve Oakland, 1997;Komarraju vd., 2011;Özgen ve Alkan, 2014;Reynolds ve Gerstein, 1992;Uzuntiryaki, 2007;Yazıcılar ve Güven, 2009), daha yüksek akademik başarın elde edildiği belirtilmektedir. Bu çalışmada ayrıştırma öğrenme stiline sahip öğrencilerin genel akademik başarı puan ortalamaları diğer öğrenme stillerine sahip öğrencilerin genel akademik başarı puan ortalamalarından yüksektir.…”
Section: Discussionunclassified
“…Öğrenme stilleri ile ilgili daha önce yapılan çalışmalar (Birrell, Phillips ve Stottc, 1985;Burns, Johnson ve Gable, 1998;Fan, Xiao ve Su, 2015;Gökalp, 2013;Hein ve Budny, 2000;Horton ve Oakland, 1997;Komarraju, Karau, Schmeck ve Avdic, 2011;Reynolds ve Gerstein, 1992;Uzuntiryaki, 2007;Yazıcılar ve Güven, 2009), öğrencilerin öğrenme özelliklerine uygun hazırlanmış programlarda daha yüksek akademik başarı elde edildiğini ortaya koymaktadır. Bu açıdan bakıldığında bu çalışma, spor lisesi öğrencilerinin öğrenme özelliklerinin belirlenmesi, eğitimcilere yol göstermesi ve eğitim politikalarını belirleyenlerin öğrenme ortamında birtakım tedbirler alabilmesine olanak vermesi açısından önemli olduğu düşünülebilir.…”
unclassified
“…These studies reveal that students learn more effectively (e.g. increasing their academic achievement and having positive attitudes toward learning) in an instructional design that matches their learning styles (Aydıntan et al, 2012;Bozkurt & Aydoğdu, 2009;Constantinidou & Baker, 2002;Demir & Usta, 2011;Gökalp, 2013;Kaf Hasırcı, 2005;Mahiroğlu & Bayır, 2009;Özgen & Alkan, 2014;Yılmaz Soylu & Akkoyunlu, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In the national literature, it was reported that quasi-experimental design (Aktaş & Bilgin, 2012;Balcı, 2013;Mutlu & Okur, 2012;Önder, 2012;Şeker & Yılmaz, 2010;Tatar & Dikici, 2009), trueexperimental design (Aslan, 2012;Gökova, 2010;Günay Ermurat, 2008;Özdemir, 2009; and weak experimental design (Çolak, 2013;Gökalp, 2013;Uyangör & Dikkartın, 2009;Yılmaz Soylu & Akkoyunlu, 2002) were used in the studies investigating the effect of learning styles models on academic achievement. According to Büyüköztürk, Kılıç Çakmak, Akgün, Karadeniz, and Demirel (2008), in weak experimental design the comparison is made in one group by applying pretest and posttest whereas in quasi-experimental design there are two groupsone treatment group and one control group selected by non-random method-and a between-group comparison is made.…”
Section: Experimental Design and Academic Achievementmentioning
confidence: 99%
“…A significant difference was observed between the pre-test and post-test learning of the sampled students. These findings suggested that academic performance can be enhanced by opting the appropriate learning style [19].…”
mentioning
confidence: 93%